Reconhecimento de entidades nomeadas aplicado em prontuários médicos - Souza, Thais Cristina Cardozo de (Universidade Federal de São Carlos, 2022)
A named entity is a real-world object, such as a person (e.g. Alan Turing), a location (e.g. London), or an organization (e.g. UFSCar). Named Entity Recognition (NER) is a subarea of Natural Language Processing (NLP) whose purpose is to identify various named entities that appear in text. This work proposes to detail the steps for the use of Named Entity Recognition. Its applicability is demonstrated in real anonymized medical records that contain textual information about patients.
Named entity recognition applied to medical records
Keywords: Processamento de linguagem natural; Reconhecimento de entidades nomeadas; Redes neurais; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::ANALISE DE DADOS